The Effects of Low Cash Flow on Health Service Delivery and Drug Availability at Ga West Central Hospital - Gyimah, William Afful; Luolin, Zhou (Advances in Social Sciences Research Journal, 2026)
The concept of a cash flow system is one of the most controversial issues in the health sector. The paradigm focus has been on healthcare utilization and human security until a shift in recent times. The paradigm shift in recent times has linked the funding of the public health notion to a global approach for ameliorating the scarcity of patients’ drugs as well as the underutilization of health care services. The study aimed at investigating the impacts of central governments’ low cash flow on health service delivery and the availability of patients’ drugs. With a random sampling, participants were selected to partake in the study with a standardized quantitative questionnaire to measure the variables involved in the study and a regression technique to analyze the data. The results reveal that low cash flow has a negative impact to the health service delivery by any health care center, as it also limits the availability of patients’ drugs. The study is essential to in restructuring of the cash flow system by the central government towards health care.